WHAT LED FINANCIAL CRISIS? EVIDENCE WITH RISK MITIGATION & PREVENTION POLICY RESPONSE - Ramadhan, R. Audi Cahya Lucky (Universitas Sarjanawiyata Tamansiswa, 2024)
Financial crises often have a negative impact on the economy and leave a trail of destruction and trigger social unrest, Thus it is necessary to prevent and mitigate the risk of financial crises with optimal policies. Therefore, this research aims to identify factors that can influence a financial crisis in a country and provide policy recommendations based on mitigating and preventing crisis risks based on cases that have occurred. The method used in this research is literature study and case study by collecting data, reports and previous research that are relevant to cases of global and national financial crises. The results of this research are based on a discussion of the relevance of certain financial crisis cases by providing optimal policies by considering risk mitigation and prevention. The implications for stakeholders affected by the financial crisis are also discussed. This research is expected to contribute to formulating effective and sustainable recovery strategies, as well as building stronger economic and social resilience on future crises.